2007 IEEE/SEMI Advanced Semiconductor Manufacturing Conference (ASMC) 2007
DOI: 10.1109/asmc.2007.375090
|View full text |Cite
|
Sign up to set email alerts
|

Novel Thermally-Stable Hafnium and Zirconium ALD Precursors

Abstract: Topic: Advanced Processes and Materials AbstractAtomic Layer Deposition (ALD) of Hf and Zr oxide films is of considerable interest and promise for future generation Metal-Insulator-Metal (MIM) structures in memory applications. Hafnium and zirconium alkylamides such as tetrakis(ethylmethylamino) hafnium (TEMAH) and tetrakis(ethylmethylamino) zirconium (TEMAZ) are the most considered precursors. However, their relatively low thermal stability might become a drawback under heated distribution conditions that cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…, ( E )- N ′-hydroxy- N , N -dimethylacetimidamide (mdaoH) and ( Z )- N ′-hydroxy- N , N -dimethylpivalimidamide (tdaoH), along with their Zr and Hf homoleptic complexes, Zr­(mdao) 4 ( 1 ), Hf­(mdao) 4 ( 2 ), Zr­(tdao) 4 ( 3 ), and Hf­(tdao) 4 ( 4 ). It is well-known that the replacement of one ligand with a cyclopentadienyl (Cp) ligand enhances the thermal stability and volatility of the given precursors. , Furthermore, in the previous study, we also confirmed that the melting point decreased when a Cp ligand was introduced into the respective homoleptic solid compound to yield the corresponding heteroleptic . Therefore, it was expected that the mixed ligand systems combining amidoxime and Cp ligand would provide improved physical properties.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…, ( E )- N ′-hydroxy- N , N -dimethylacetimidamide (mdaoH) and ( Z )- N ′-hydroxy- N , N -dimethylpivalimidamide (tdaoH), along with their Zr and Hf homoleptic complexes, Zr­(mdao) 4 ( 1 ), Hf­(mdao) 4 ( 2 ), Zr­(tdao) 4 ( 3 ), and Hf­(tdao) 4 ( 4 ). It is well-known that the replacement of one ligand with a cyclopentadienyl (Cp) ligand enhances the thermal stability and volatility of the given precursors. , Furthermore, in the previous study, we also confirmed that the melting point decreased when a Cp ligand was introduced into the respective homoleptic solid compound to yield the corresponding heteroleptic . Therefore, it was expected that the mixed ligand systems combining amidoxime and Cp ligand would provide improved physical properties.…”
Section: Introductionsupporting
confidence: 81%
“…It is wellknown that the replacement of one ligand with a cyclopentadienyl (Cp) ligand enhances the thermal stability and volatility of the given precursors. 28,29 Furthermore, in the previous study, we also confirmed that the melting point decreased when a Cp ligand was introduced into the respective homoleptic solid compound to yield the corresponding heteroleptic. 24 Therefore, it was expected that the mixed ligand systems combining amidoxime and Cp ligand would provide improved physical properties.…”
Section: Introductionsupporting
confidence: 79%
“…The thermal stability of a precursor must be discussed for a successful ALD process, and many studies have already been carried out [25][26][27][28]. However, most of the studies related to the thermal stability of precursors have measured the decomposition temperature using thermogravimetric analysis (TGA) or studied the decomposition behavior in the gas phase by using quadrupole mass spectrometry (QMS) and a quartz crystal microbalance (QCM) [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The focus of this manuscript is the chemistry of pentakis(dimethylamido)tantalum (PDMAT), Ta[N(CH 3 ) 2 ] 5 , on tantalum surfaces. PDMAT is one of the most common precursors used for TaN deposition. , The surface chemistry of PDMAT is also closely related to that of other similar precursors such as tetrakis(dimethylamido)titanium (TDMAT), Ti[N(CH 3 ) 2 ] 4 , and tetrakis(dimethylamido)hafnium (TDMAH), Hf[N(CH 3 ) 2 ] 4 , which contain the same dimethylamido ligands, and even to that of tetrakis(methylethylamido)titanium (TEMAT), Ti[N(CH 3 )(C 2 H 5 )] 4 , tetrakis(methylethylamido)zirconium (TEMAZ), Zr[N(CH 3 )(C 2 H 5 )] 4 , and tetrakis(methylethylamido)hafnium (TEMAH), Hf[N(CH 3 )(C 2 H 5 )] 4 , , which have closely related amido groups.…”
Section: Introductionmentioning
confidence: 99%